Faktor-faktor yang mempengaruhi kelengkapan vaksinasi dasar pada bayi hingga usia 12 bulan - Riska Wandini; Yeni Koto; Mutiara Veny Yulia (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Factors influencing basic vaccination coverage of babies up to 12 months of ageBackground: Based on pre-survey conducted on six center for pre and post natal health cares at working area of Permata Health Center of Sukarame, there were 153 out of 346 babies receiving complete vaccination up to 12 months of agePurpose: To identify the influence of factors basic vaccination coverage of babies up to 12 months of ageMethod: A quantitative and analytical survey with cross sectional approach. The population was mothers and their babies with the sample was of 142 respondents and taken by purposive sampling. The statistical analysis was chi square.Results: Shows as 109 (76.8%) of respondents had a poor knowledge, 76 (53,5%) negative attitudes, 83 (58,5%); had low educational background, 50 (35,2%) lived in a supportive environment, and 55 infants (38.7%) received uncomplete basic vaccinations. The relationship varies from knowledge with a p value of 0,000 (α <0.05), attitudes to a value of p 0,000 (α <0.05), level of education with a value of p 0,000 (α <0.05), and environment with a value of p 0,000 ( α <0.05).Conclusion: Indicated that there were correlations among knowledge, attitude, education level and environment influencing basic vaccination coverage of babies up to 12 months of age. The health practitioners are suggested to provide a comprehensible knowledge for the parent on vaccination for immunities from any diseases of their babies.Keywords: Basic vaccination; Babies; ParentPendahuluan: Berdasarkan hasil prasurvey di 6 posyandu Wilayah Puskesmas Permata Sukarame, hanya terdapat 153 dari 346 bayi yang telah mendapatkan vaksinasi lengkap hingga usia 12 bulan.Tujuan: Untuk mengetahui faktor-faktor yang mempengaruhi kelengkapan vaksinasi dasar pada bayi hingga usia 12 bulanMetode: Penelitian kuantitatif dengan desain Survei Analitik dengan pendekatan cross sectional. Populasinya semua ibu dan bayi berumur hingga 12 bulan dan sampelnya 142 responden dengan cara purposive sampling. Uji statistik menggunakan uji chi squareHasil: Didapatkan 109 (76.8%) responden memiliki pengetahuan yang buruk, 76 (53,5%) sikap negatif, 83 (58,5%); memiliki latar belakang pendidikan rendah, 50 (35,2%) tinggal di lingkungan yang mendukung, dan 55 bayi (38,7%) tidak lengkap vaksinasi dasar. Hubungan bervariasi dari pengetahuan dengan nilai p 0,000 (α <0,05), sikap dengan nilai p 0,000 (α <0,05), tingkat pendidikan dengan nilai p 0,000 (α <0,05), dan lingkungan dengan nilai p p 0,000 (α <0,05).Simpulan: Adanya korelasi antara pengetahuan, sikap, tingkat pendidikan dan lingkungan yang mempengaruhi cakupan vaksinasi dasar bayi hingga usia 12 bulan. Para praktisi kesehatan disarankan untuk memberikan pengetahuan yang komprehensif bagi orang tua mengenai vaksinasi untuk kekebalan/imunitas dari penyakit apa pun pada bayi mereka.